Gender differences in perceptions of leadership and their influence on motivation among faculty members of Taif University - Alharthi, Fawziah B. (Frontiers in Psychology, 2024)
This study investigates gender differences in perceptions of leadership styles and their impact on faculty motivation at Taif University, Saudi Arabia, within the context of Islamic higher education. Utilizing a quantitative research method approach, the researcher gathered survey responses from 74 faculty members at Taif University. The investigation focused on three main areas: the significant gender differences in perceptions of leadership styles among faculty members at Taif University; the tendency of female faculty members to perceive transformational leadership styles more positively than their male counterparts; and the more favorable response of male faculty members to transactional leadership styles compared to female faculty members. The results of this study revealed significant gender differences, with female faculty members showing a preference for transformational leadership, while male faculty members responded more positively to transactional leadership. By adopting these findings, leaders at Taif University can participate positively on faculty members' motivation. In addition to that leadership practices can move towards sustainability, ensuring the continuous development of faculty, students, and resources. These findings contribute to a deeper understanding of gender-based perceptions of leadership in an Islamic higher education setting and offer strategies for enhancing faculty motivation through tailored leadership approaches.